The Influence of Demographic Factors on the Location of Bisphosphonate-related Atypical Femoral Fractures - Yuan, Wei (Indian J Orthop, 2020)
BACKGROUND: The location of bisphosphonate-related atypical femoral fractures (AFFs) is related to the femoral bow. Other factors that might also be related to the distribution of AFFs are not well studied. In this study, we attempt to define the demographic factors that influence the distribution AFFs in our local population. MATERIALS AND METHODS: The medical records of all the patients diagnosed with AFFs treated in our institution between 2008 and 2017 were retrospectively reviewed and divided based on fracture location into subtrochanteric and mid-shaft groups. Demographic data were collected and compared between the two groups. Independent factors affecting the location of AFFs were identified via multivariate analysis. RESULTS: Seventy-nine AFFs in 71 patients were included. Thirty-two fractures occurred at the subtrochanteric region and 47 occurred at the mid-shaft. Age, bone density, anterior femoral bow and lateral femoral bow were significantly different between the two groups, whereas height, weight, body mass index, presence of prodromal symptoms, type and duration of bisphosphonates were not significantly different. Multivariate analysis showed anterior femoral bow was the only independent factor associated with the location of AFFs. CONCLUSIONS: Anterior femoral bow is the only factor that can predict the location of AFFs. In our population, other demographic factors were not found to be predictive.